(untitled) (JURNAL HANDAYANI PGSD FIP UNIMED, 2019)
Abstract : Improving the Ability of English Language Teachers in Designing RPP 2013 Curriculum Through Continuous Guidance Activities. This study aims to improve the ability of teachers in Tebingtinggi City 5 Middle School in preparing learning implementation plans (RPP) using the 2013 curriculum through mentoring activities. The subject of this study is an English teacher who teaches in the State Middle School 5 in Tebingtinggi in the 2016/2017 learning year, which amounts to 5 teachers. This study uses qualitative descriptive analysis techniques. Data analysis in this study was collected through performance activities, observation sheets, interviews and documentation. Continuous guidance activities carried out on English language teachers in the 2016/2017 learning year conducted at Tebingtinggi 5 Public Middle School through continuous guidance activities can improve the ability of teachers to prepare lesson plans using the 2013 curriculum. This can be seen from the results of assessments and observations made by researchers if before the assistance is carried out the number of teachers who are able to make lesson plans using the 2013 curriculum can be said to be nonexistent then after the second cycle, all 5 English teachers have been able to prepare lesson plans using the 2013 curriculum. Keywords : RPP, 2013 Curriculum, Sustainable Guidance Abstrak : Peningkatan Kemampuan Guru Bahasa Inggris Dalam Merancang RPP Kurikulum 2013 Melalui Kegiatan Bimbingan Berkelanjutan. Penelitian ini bertujuan untuk meningkatkan kemampuan guru-guru SMP Negeri 5 kota Tebingtinggi dalam menyusun rencana pelaksanaan pembelajaran ( RPP ) menggunakan kurikulum 2013 melalui kegiatan pendampingan. Yang menjadi subjek pada penelitian ini adalah guru bahasa Inggris yang mengajar di SMP Negeri 5 kota Tebingtinggi tahun pembelajaran 2016/2017 yang berjumlah 5 guru. Penelitian ini menggunakan teknik analisis deskriptif kualitatif. Analisis data pada penelitian ini dikumpulkan melalui kegiatan unjuk kerja, lembar observasi, wawancara serta dokumentasi. Kegiatan bimbingan berkelanjutan yang dilakukan terhadap guru bahasa Inggris tahun pembelajaran 2016/2017 yang dilakukan di SMP Negeri 5 kota Tebingtinggi melalui kegiatan bimbingan berkelanjutan dapat meningkatkan kemampuan guru dalam menyusun RPP menggunakan kurikulum 2013. Hal ini dapat terlihat dari hasil penilaian dan observasi yang dilakukan oleh peneliti jika sebelum pendampingan dilakukan jumlah guru yang mampu membuat RPP dengan menggunakan kurikulum 2013 bisa dikatakan tidak ada sama sekali maka setelah siklus II dilaksanakan seluruh guru bahasa Inggris sebanyak 5 guru telah mampu menyusun RPP dengan menggunakan kurikulum 2013. Kata Kunci : RPP, Kurikulum 2013, Bimbingan Berkelanjutan